Caring Cards: Preventing Patient Harm Through the Heart of Nursing. Issue 3 (July 2018) - Gould, Meredith; Mann, Marci; Martin, Heather; Erwin, Rachael; Schultz, Ron; Swanson, Kristen
Abstract : The use of "Caring Cards" is a unique innovation, which builds on reliable Lean processes. It adds the way we emotionally care for people to a Lean methodology. This article describes how the foundational constructs of nursing theory are paired with aspects of universal fall precautions. In a pilot prioritizing Caring Cards, conversations between leaders and staff provide a way for the nurse to describe his or her critical thinking about fall prevention that is individualized to a patient. Leaders collect information on barriers to care and demonstrate follow-up actions to staff members who raise concerns. The system allows for structured leader and staff interactions that are coaching and mentoring in nature. These support an environment where nurses care for patients, while leaders also care for staff. By partnering Lean methodology with the heart of nursing, patient care can be improved. The pilot project utilizing this methodology was performed on a neurological unit. It resulted in a dramatic reduction in falls. The unassisted patient fall rate per 1000 patient-days dropped from 11.60 to 5.81 falls, a 50% reduction.